Evaluasi Kinerja Peternak Mitra Ayam Ras Pedaging - Arum, K. T.; Cahyadi, E. R.; Basith, A. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2017)
Broiler chicken had a great performance with unique characteristics like rapid growth, had a thick meat, and also had a relatively short breeding time. The breeding management became one of the farmers key success in describing their management system effectively. One of the management function was the evaluation, thus the research purpose was to evaluate the performance of partnership farmers as the partner of PT XYZ. This research was using the observation and interview methods to the company’s side and also the ones who was involved in the farmers performance evaluation process. The data that was used in this research was the secondary data that was gathered from the company’s yearly report, and was seen  by the farmers index performance (IP). This study took 36 breeders as the sample, 216 periods in 2017 for 6 production cycles. Data were analyzed using a control chart. Data analysis indicates IP Score less than 300 goes to underperformed, 301-325 is considered enough, while a score of 326 - 350 goes to good. As for great and outstanding there are no farmers yet in those segments. The highest IP score for partnership farmers is 335 and the lowest was 277. Partnership farmers in category "enough" are 69,44%, "good" 11,11% and "underperformed" 10,44%. Upper Control Limit (UCL) is 344,36 and Low Control Limit (LCL) is 278,65 wit Mean value of 311,50. There are two points less than LCL, in 19th  and 210th points, scoring 277 and 278.